The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1242/dev.183392
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase drives early-onset intestinal failure in a mouse model of congenital tufting enteropathy

Abstract: Syndromic congenital tufting enteropathy (CTE) is a life-threatening recessive human genetic disorder that is caused by mutations in SPINT2, encoding the protease inhibitor HAI-2, and is characterized by severe intestinal dysfunction. We recently reported the generation of a Spint2-deficient mouse model of CTE. Here, we show that the CTE-associated early-onset intestinal failure and lethality of Spint2deficient mice is caused by unchecked activity of the serine protease matriptase. Macroscopic and histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Indeed, ablation of St14 /matriptase in the intestinal epithelium impaired the barrier function and induced mucosal inflammation, eventually resulting in the formation of colon adenocarcinoma in mice . Excess matriptase activity also leads to the disturbance of epithelial integrity in the intestine . Moreover, matriptase is known to be upregulated in various human cancers and deregulated activities of matriptase contribute to tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ablation of St14 /matriptase in the intestinal epithelium impaired the barrier function and induced mucosal inflammation, eventually resulting in the formation of colon adenocarcinoma in mice . Excess matriptase activity also leads to the disturbance of epithelial integrity in the intestine . Moreover, matriptase is known to be upregulated in various human cancers and deregulated activities of matriptase contribute to tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Matriptase was found to catalyze dibasic cleavage of EpCAM between arginines 80 and 81, reducing the interaction of EpCAM with claudin-7 inducing its destabilization. This event has the potential to contribute to the disruption of the epithelial integrity of mouse intestine in CTE [156,157].…”
Section: Epcam As a Target In Clinical Trials For Cancer Therapymentioning
confidence: 99%
“…In contrast to what we observed in the IEC cell line Caco2 [19], HAI-2 inhibition by siRNA in keratinocytes minimally increased EpCAM and TROP2 cleavage and claudin loss. Two recent studies demonstrated that EpCAM was robustly cleaved and claudin-7 was markedly downregulated in the intestinal epithelia of SPINT2 KO mice [20,35]. The reasons for the discrepancy regarding HAI-2's role in inhibiting matriptase cleavage of TROP proteins in IECs and in keratinocytes are unknown.…”
Section: Discussionmentioning
confidence: 99%